Canada : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper assesses Canada's post-crisis export performance of non-energy products using model-based benchmarks. Specifically, the analysis explores whether the pre-crisis relationship between Canada's non-energy exports and their determinants still holds in the post-crisis period. At the aggregate level, Canada's non-energy exports do not seem to have performed particularly poorly relative to the benchmark. Of the 23 non-energy products, five products outperformed their respective benchmarks both in growth and level terms, while seven products underperformed by the same measures. The statistical tests show that a total of 13 products had a structural break during the global financial crisis of 2007-2008. At the aggregate level, the time paths of non-energy exports' elasticities confirm the increasing importance of US business investment. The findings at the product level reinforce those at the aggregate level, but also reveal some interesting differences between across products. A decomposition of Canada's non-energy export growth based on the post-crisis elasticities confirms the significant contributions from US consumption and non-US demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet